Role of ferroptosis and immune infiltration in intervertebral disc degeneration: novel insights from bioinformatics analyses - Liu, Xiao-Wei; Xu, Hao-Wei; Yi, Yu-Yang; Zhang, Shu-Bao; Wang, Shan-Jin (Frontiers in Cell and Developmental Biology, 2023)
Background: Intervertebral disc degeneration (IVDD), which contributes to stenosis of the spinal segment, commonly causes lower back pain. The process of IVDD degradation entails gradual structural adjustments accompanied by extreme transformations in metabolic homeostasis. However, the molecular and cellular mechanisms associated with IVDD are poorly understood. Methods: The RNA-sequencing datasets GSE34095 and GSE56081 were obtained from the Gene Expression Omnibus (GEO) database. Ferroptosis-related differentially expressed genes (DEGs) were identified from these gene sets. The protein–protein interaction (PPI) network was established and visualized using the STRING database and Cytoscape software, and the key functional modules of ferroptosis-related genes were identified. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed on the DEGs. Weighted gene co-expression network analysis (WGCNA), immune infiltration analysis in the GEO database, and other GSE series were used as validation datasets. The xCELL algorithm was performed to investigate the immune cell infiltration differences between the degenerated IVDD and control groups. Results: The major genes involved in nucleus pulposus tissue immune infiltration and ferroptosis-related genes were mined by bioinformatics analysis. A total of 3,056 DEGs were obtained between the IVDD tissue and control groups. The DEGs were enriched in the cell cycle; apoptosis; necroptosis; and the PI3K-Akt, Hippo, and HIF-1 signaling pathways. PCR and Western blot techniques were utilized to confirm the differential ferroptosis-related genes. The results indicated that the protein expression levels of NCOA4 and PCBP1 were elevated, while the protein expression level of GPX4 was reduced in NPCs following IL-1β treatment. Our study has found that severe disc tissue degeneration leads to a noteworthy increase in the expression of CD8A in naive T cells, CCR7 in memory CD4+ cells, GZMB in natural killer (NK) cells, and CD163 and CD45 in macrophages. Conclusion: Our data demonstrate that ferroptosis occurs in IVDD, suggesting that ferroptosis may also increase IVDD improvement by triggering immune infiltration. This work was conducted to further understand IVDD pathogenesis and identify new treatment strategies.